2016
DOI: 10.1016/j.jweia.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the interaction between tandem wind turbines

Abstract: Two model wind turbines operating in tandem are simulated using Tenasi, a nodecentered, finite volume unstructured flow solver. The turbine blades are designed using the NREL S826 airfoils. The entire test section of the wind tunnel is simulated since the blockage (based on swept area of the rotor and tower area) was 12%. The simulations included the tunnel walls, wind turbine blades, hubs, nacelles and towers. Detailed experimental data is available for a variety of flow conditions (varying tip-speed-ratios).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Rosenberg et al [51] extended efforts of the Vortex Lattice Method (VLM) to analyze aerodynamics of dual-rotor wind turbines. Sreenivas et al [52] studied the interaction between two wind turbines (NREL S826 airfoils) operating in tandem for TSR of 2.5, 4, and 7 in a wind tunnel speed at 10 m•s −1 . Larsen et al [53] reviewed several studies in wake aerodynamics.…”
Section: Nrel 5 Mwmentioning
confidence: 99%
“…Rosenberg et al [51] extended efforts of the Vortex Lattice Method (VLM) to analyze aerodynamics of dual-rotor wind turbines. Sreenivas et al [52] studied the interaction between two wind turbines (NREL S826 airfoils) operating in tandem for TSR of 2.5, 4, and 7 in a wind tunnel speed at 10 m•s −1 . Larsen et al [53] reviewed several studies in wake aerodynamics.…”
Section: Nrel 5 Mwmentioning
confidence: 99%
“…Sreenivas et al 30 showed that it is possible to reproduce accurately two interacting wind turbines with blade-resolved numerical simulations, even if the downstream turbine is located as near as 3D from the upstream turbine. Mycek et al 31 investigated turbine-wake interaction more thoroughly by comparing the upstream and downstream turbines, by varying the distance between the two turbines and by including the effect of upstream turbulence conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to study the wake dynamics we utilized the experimental results conducted by the fellow researchers at Norwegian University of Sciences & Technology (NTNU) [12]. These experimental campaigns, known as Blind Test, have become popular for benchmarking and validating the performance evaluation of small wind turbines [1], [2], [13], [14], [15]. Previous studies also incorporated the effect of tower and tunnel blockage using actuator line modeling [16], [17].…”
Section: Introduction and Objectivementioning
confidence: 99%